An Acute Exposure to Muscle Vibration Decreases Knee Extensors Force Production and Modulates Associated Central Nervous System Excitability - Souron, Robin; Besson, Thibault; McNeil, Chris J.; Lapole, Thomas; Millet, Guillaume Y. (Frontiers in Human Neuroscience, 2017)
Local vibration (LV) has been recently validated as an efficient training method to improve muscle strength. Understanding the acute effects may help elucidate the mechanism(s). This study aimed to investigate the effects of a single bout of prolonged LV on knee extensor force production and corticospinal responsiveness of vastus lateralis and rectus femoris muscles in healthy young and old adults. Across two visits, 23 adult subjects (20⎯75 years old) performed pre- and post-test measurements, separated by 30-min of either rest (control; CON) or LV. Maximal voluntary contraction (MVC) force was assessed and transcranial magnetic stimulation (TMS) was used to evaluate cortical voluntary activation (VATMS) as well as the motor evoked potential (MEP) and silent period (SP). In 11 young adults, thoracic electrical stimulation was used to assess the thoracic motor evoked potential (TMEP). Although MVC decreased after both CON (-6.3 ± 4.4%, p=0.01) and LV (-12.9 ± 7.7%, p<0.001), the MVC loss was greater after LV (p=0.001). Normalised maximal EMG activity decreased after LV for both vastus lateralis (-25.1 ± 10.7%) and rectus femoris (-20.9 ± 16.5%) (p<0.001), while it was unchanged after CON (p=0.32). For rectus femoris, the TMEP and MEP/TMEP ratio decreased (p=0.01) and increased (p=0.01) after LV, respectively. Both measures were unchanged for vastus lateralis (p=0.27 and p=0.15, respectively). No changes were reported for TMS-related parameters. These results confirm our hypothesis that modulations within the central nervous system would accompany the significant reduction of maximal voluntary force. A reduced motoneuron excitability seems to explain the decreased MVC after prolonged local vibration, as suggested by reductions in maximal EMG (all subjects) and TMEP area (data from 11 young subjects). A concomitant increased cortical excitability seems to compensate for lower excitability at the spinal level.